(untitled) (Physical Education, Health and Social Sciences, 2026)
This paper has discussed how artificial intelligence (AI) based teaching mechanisms can be used to help students with learning disabilities in classrooms. The research in question sought to investigate the perceptions of teachers on the efficacy of artificial intelligence in supporting personalized learning, adaptive support, inclusive practices, and innovation in learning. The quantitative research method was used, and a descriptive survey design was utilized. The self-developed questionnaire comprised 40 items and was used to collect data of 350 teachers. The results showed that AI-based teaching methods were perceived positively as effectively to enhance lesson plans, differentiation instructions, student learning, and learning challenges. The findings also indicated that individualized learning and supportive provision were good predictors of enhanced learning opportunities among such students. Overall, the researchers found that AI-based teaching methods had the potential to become effective tools in improving inclusive teaching processes under the conditions of appropriate training, infrastructure, and institutional assistance. The research suggested training, policy support, and enhanced digital resources to implement effective implementation.